Premalignant lesions of the oral cavity: current perspectives - Swain, Santosh Kumar (International Journal of Research in Medical Sciences, 2021)
Premalignant lesions of the oral cavity are also called as potentially malignant disorders. The common premalignant lesions of the oral cavity include leukoplakia, oral submucous fibrosis (OSMF) and oral erythroplakia. These lesions have a very high malignant transformation rate. The exact etiological factors for development of the premalignant lesions of the oral cavity are not fully understood till date. Use of tobacco, alcohol drinking, chewing betel quid containing areca nut and solar rays are important etiological factors for resulting the premalignant lesions of the oral cavity. Early diagnosis is an important step for preventing the malignant transformations of these lesions and can be also life-saving. There are several treatment options including conservative to surgical for eliminating the premalignant lesions of the oral cavity. The aim of this study was to discuss the details of epidemiology, etiopathology, clinical presentations, diagnosis and current treatment of the premalignant lesions of the oral cavity.